Insider trading in the KLSE market. - Lim, Sylvia Li Shin. (2008)
To analyse insider trading in KLSE, using an event study. To find abnormal returns gained by insiders. Test for strong form EMH. Timing of transactions with privileged information. Outsiders who follow insider trades in order to determine if market is semi-strong form.